The impact of recreational cannabinoid legalization on utilization in a pregnant population - Jacob Torres; Colton Miller; Michael Apostol; Jessica Gross; Jessie R. Maxwell; Jessie R. Maxwell (Frontiers Media S.A., 2024)
BackgroundMarijuana potency and utilization both continue to increase across the United States. While the overall prevalence of cannabinoid utilization during pregnancy has been surveyed in various studies, the direct impact of changing governmental policies on pregnancy use is less characterized. Thus, we aimed to investigate how the legalization of recreational cannabinoid products impacted use during pregnancy in the state of New Mexico.MethodsParticipants who had a live birth during two study epochs were included: pre-legalization (Epoch 1: 1 January 2019-31 March 2021) and post-legalization (Epoch 2: 1 November 2021-30 November 2022). Participants were further divided into case group [prenatal cannabinoid exposure (PCE)] vs. control (no PCE), with cases being identified by documented self-report or a positive laboratory toxicology test for cannabinoid use during pregnancy.ResultsA total of 1,191 maternal/infant dyads were included in Epoch 1, and 378 maternal/infant dyads were included in Epoch 2. In Epoch 1, 788 dyads were controls with 403 cases, while Epoch 2 had 292 controls and 86 cases. Interestingly there was a significant decrease in self-report or positive laboratory toxicology tests in Epoch 2 compared to Epoch 1. Infants born following PCE in both Epoch groups were more commonly born via Cesarean section, had significantly smaller birth weight, length, and head circumference as well as significantly lower Apgar scores at 1 and 5 min.ConclusionThe finding of decreased reported cannabinoid use in the post-legalization group is contradictory to previous studies which have shown increased rates of cannabinoid use after legalization. This could be due to multiple factors including changes in screening practices, the COVID-19 pandemic, and lack of commercialization of THC products. Additional studies are needed to further characterize how changing governmental policies impacts utilization during pregnancy.